Consumer Buying Behavior during the New Normal through Online Application from 7-Eleven Convenience Stores in Mueang District, Chonburi Province - Matman, Phawinee; Kumsumran, Somkiat (Rajamangala University of Technology Tawan-ok Social Science Journal, 2025)
The objective of the research were to study personal demographic factors and marketing mix factors that influence consumer behavior under the new normal towards purchasing products through online application from 7-Eleven (7-11) in Mueang District Chonburi Province. The data were collected from a sample of 400 people using various statistical tools, including frequency, percentage, mean, standard deviation, Independent-Samples t-test, One-Way ANOVA, and multiple regression analysis. The results showed that there were 64% female, 36% male, aged between 25 - 35 years, with bachelor's degree level, being an employee of a private company, average monthly income is 15,001- 25,000 baht, composed of 3 family members, and home is the location where most products are delivered. The results of the demographic analysis found that only an income factor influences consumers’ behavior under the new normal of purchasing products through online application from 7-Eleven convenience stores (7-11) and from the results of the analysis of marketing mix factors which influence consumer behavior under the new normal towards purchasing products through online applications from 7-Eleven convenience stores (7-11) in Mueang District Chonburi Province using the multiple regression method. Statistical significance was set at 0.05. The results of the study found that there are value factors that customers receive, followed by convenience, comfort, and satisfaction in responding to customer needs statically significant.